2022
DOI: 10.3390/rs14205279
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Patterns and Driving Factors of Ecological Vulnerability on the Qinghai-Tibet Plateau Based on the Google Earth Engine

Abstract: With the background of climate change and intensified human activities, environmental problems are becoming increasingly prominent on the Qinghai-Tibet Plateau (QTP). For the development of efficient environmental policies and protection measures, quick and accurate assessments of the spatiotemporal patterns in ecological vulnerability are crucial. Based on the Google Earth Engine (GEE) platform, we used Moderate Resolution Imaging Spectroradiometer (MODIS), Shuttle Radar Topography Mission (SRTM), and human f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 71 publications
0
0
0
Order By: Relevance
“…On the other hand, mapping human footprint data based on eight human activity variables, including population density, environmental buildings, and land use data, can lead to a more comprehensive quantification of human activities [21]. Human footprint data have been used to evaluate ecological vulnerability on the Tibetan Plateau [40], and explore arable land expansion [41]. In this study, we use human footprint data to directly quantify human activities and accurately assess their impact on vegetation ecology EQI.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, mapping human footprint data based on eight human activity variables, including population density, environmental buildings, and land use data, can lead to a more comprehensive quantification of human activities [21]. Human footprint data have been used to evaluate ecological vulnerability on the Tibetan Plateau [40], and explore arable land expansion [41]. In this study, we use human footprint data to directly quantify human activities and accurately assess their impact on vegetation ecology EQI.…”
Section: Discussionmentioning
confidence: 99%
“…Global Moran's I is a statistical measure that can be used to describe the spatial correlation of geographic phenomena at a global scale. It evaluates the spatial clustering of EEQ by comparing the RSEI values of a particular spatial unit with those of its neighboring units [22,58]. It ranges from −1 to 1.…”
Section: Spatial Autocorrelation Analysismentioning
confidence: 99%
“…Our results of ARESI trend analysis indicated that the significant degradation of China's ecological environment quality mainly occurred in the northern Tianshan mountain range, the northern part of the Greater Khingan Mountains in Northeast China, the Qinghai-Tibet Plateau, the North China Plain, the Yangtze River delta, and some central urban agglomerations. The reasons for the deterioration of the ecological environment are divided into three categories: (1) Poor natural conditions cause ARSEI decline (Zhao et al, 2022). For example, the plateau ecosystem of the Qinghai-Tibetan Plateau is fragile and sensitive to climate change.…”
Section: Factors Influencing Spatiotemporal Variation Of Arseimentioning
confidence: 99%